Improving of boiler fuel quality by additives - E. R. Zvereva; O. S. Zueva; R. V. Khabibullina; Z. F. Khatmullina; E. S. Dremicheva (Известия высших учебных заведений: Проблемы энергетики)
The possibility of improving the rheological properties of the fuel oil by the use of additives of different nature including nanoparticles has been shown. Technological schemes additive dosing have been designed. The evaluation of cost-effectiveness of adding to fuel oil additives based on solid carbonate slurry and the liquid additive Diproksamin-157 have been carried out.